Low-load resistance training with blood flow restriction versus traditional training exercises in patients with knee osteoarthritis - Mai Abdelkader; Enas Fawzy; Abdulrahman Shabara; Nabil A. Mohamed (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.